An analysis of statutory provisions and case law on trade marks registration under the Nigerian trade marks act (2018)
The legal implication of trade mark registration is to have exclusive right to use the mark, and if need be, assign the mark to another person for use. The objective of 'trademarks registration is to enhance the economic efficiency of the market place by making the products and producers easier to identify by consumers. The aim of this paper is to analyze the statutory provisions and case law on trade mark registration in Nigeria. In doing this, the pertinent questions which this paper seeks to interrogate among others are: What can be or cannot be registered as trade mark? What is the rationale for trade mark registration? What are the procedures for trade mark registration and the legal effect of registration of trade mark? To answer these questions, this paper explains the meaning and registration of trademark, the paper highlights the advantages of trademarks registration. To understand these advantages, the article itemizes the benefits attached to the registered proprietor on the one hand and the consumers on the other hands. For the purpose of exposition of the intricacies involved in trademark registration, this paper relies heavily on case law on trademark disputes, which illustrates the points being addressed. In conclusion, the paper lists the shortcoming of the extant law on trademark registration in Nigeria with suggestions that the relevant authorities saddled with trademark administration should take steps for the review of extant trademark law in Nigeria.